Synthesis, photophysical and thermal studies of symmetrical and unsymmetrical zinc phthalocyanines - Ugur, Ahmet Lutfi; Dincer, Hatice A.; Erdogmus, Ali (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
The novel zinc phthalocyanine (3) with malonylester and chloro groups on each benzo unit was synthesized from 4-diethoxymalonyl-5-chloro-phthalonitrile (1). The unsymmetrically substituted zinc phthalocyanine (5), carrying hexylthio, malonylester and chloro groups at the periphery, was obtained from 4-diethoxymalonyl-5-chloro-phthalonitrile (1) and 4,5-bis-hexylsulfanyl-phthalonitrile (2) by a statistical condensation method as an A(3)B type unsymmetrical phthalocyanine compound. Transesterification of the malonyl esters of the new symmetrical and unsymmetrical phthalocyanines occurred during the cyclotetramerization of dinitriles with Zn(CH3COO)(2) in 1-pentanol in the presence of DBU. Octa-hexylthio-substituted zinc phthalocyanine (4) was prepared according to the literature. The photophysical and thermal properties of all the phthalocyanine complexes are described for the first time. These novel symmetrical and unsymmetrical phthalocyanine macrocycles have been characterized by a series of spectroscopic methods including H-1 NMR, electronic absorption, IR and mass spectroscopy, in addition to elemental analysis. Their narrow long wavelength absorption band shows that the bulky substituents on the periphery prevent aggregation. The unsymmetrically substituted phthalocyanine (5) gave a greater fluorescence quantum yield in chloroform than the symmetrical analogues (3 and 4). (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Unsymmetrical substituted phthalocyanine; Symmetrically substituted phthalocyanine; Aggregation; Fluorescence; Photophysics; Thermal properties; LANGMUIR-BLODGETT-FILMS; SPECTRAL PROPERTIES; OPTICAL-PROPERTIES; Chemistry; Crystallography